URGENSI TANDA TANGAN DAN MATERAI DALAM MEMBERIKAN KEPASTIAN HUKUM TERHADAP KONTRAK WARALABA (FRANCHISE) - Santoso, Lukman (Syariah: Jurnal Hukum dan Pemikiran, 2016)
This article explanes about urgency of signatures and stamp duty in giving legal certainty to the franchise contract. This theme departs from the rise of business model franchise today in Indonesia. This business is considered to minimize the risk of failure, as well as to provide various facilities. This research is a descriptive analytical research. In franchise contract are still many things that can happen in the future that might be detrimental to the parties. Therefore we need the legal umbrella to shade and protect with the aim to create a sense of fairness and legal certainty for the parties, not just for profit (profit oriented), but there is accountability for the impact of the overall business operations. To provide legal certainty every contract franchise must be in writing and include the signature and the stamp in order to obtain a force of law and can be evidence, so the purpose of legal certainty can be realized.